In Pursuit of Good Governance and Democracy in Africa: Assessing the Benchmarking Role and Mandate of the African Peer Review Mechanism (APRM) in Nigeria (Journal of Political Science and International Relationship, 2023)
The study acknowledged that the post-colonial expectations of the African societies, and the attendant result of good governance, among other values, were not just desirable, but inexorably high, given the experience of the pre-independence era as characterized by colonial imperialism. The study noted that unfortunately, such expectations may have been a mirage after all, not less for inadequate resources needed for development, but for challenges of transition on the one hand; and factors of maladministration, unbridled corruption, gross insensitivities of the post-independent leaders and their ill temperament to governance, recurring regime change by the military, self-rule, and lately, the phenomenon of rising insecurity among other inimical limitations to good governance on the African continent, on the other hand. With the establishment of the African Union (AU), which replaced the legacy Organization of African Unity (OAU) in May 2002 and now rebranded as the African Union Development Agency-New Partnership for Africa’s Development (AUDA-NEPAD), which is conceived as a strategic framework for the socio-economic development of the continent. The AUDA-NEPAD subsequently established the African Peer Review Mechanism (APRM) as an instrument for monitoring performance in governance among member states. However, the existence of the APRM has generated mixed reactions regarding pursuing its mandate among member-states. This paper sought to critically interrogate the extent to which the APRM has adequately implemented its mandate while benchmarking Nigeria, in the adherence to democratic ethos and values, and the promotion of good governance. This paper has adopted a qualitative research paradigm, relying on secondary data from relevant literature and applying an appropriate theoretical paradigm in its far reaching analysis to underpin the study. The paper concluded by professing prescriptions and perspectives, on how best to place the APRM as a continental regulatory framework for the greater well-being of Africa, particularly Nigeria, while removing the growing contradictions and challenges of governance and development at large.